New opportunities in plant microbiome engineering for increasing agricultural sustainability under stressful conditions - Afridi, Muhammad Siddique; Javed, Muhammad Ammar; Ali, Sher; De Medeiros, Flavio Henrique Vasconcelos; Ali, Baber; Salam, Abdul; Sumaira,; Marc, Romina Alina; Alkhalifah, Dalal Hussien M.; Selim, Samy; Santoyo, Gustavo (Frontiers in Plant Science, 2022)
Plant microbiome (or phytomicrobiome) engineering (PME) is an anticipated untapped alternative strategy that could be exploited for plant growth, health and productivity under different environmental conditions. It has been proven that the phytomicrobiome has crucial contributions to plant health, pathogen control and tolerance under drastic environmental (a)biotic constraints. Consistent with plant health and safety, in this article we address the fundamental role of plant microbiome and its insights in plant health and productivity. We also explore the potential of plant microbiome under environmental restrictions and the proposition of improving microbial functions that can be supportive for better plant growth and production. Understanding the crucial role of plant associated microbial communities, we propose how the associated microbial actions could be enhanced to improve plant growth-promoting mechanisms, with a particular emphasis on plant beneficial fungi. Additionally, we suggest the possible plant strategies to adapt to a harsh environment by manipulating plant microbiomes. However, our current understanding of the microbiome is still in its infancy, and the major perturbations, such as anthropocentric actions, are not fully understood. Therefore, this work highlights the importance of manipulating the beneficial plant microbiome to create more sustainable agriculture, particularly under different environmental stressors.